Perkawinan Beda Agama Berdasarkan Yurisprudensi Putusan Mahkamah Agung - Ridho, Muhamad; Amin Qodri, Muhammad; Triganda Sayuti, Ageng (Zaaken: Journal of Civil and Business Law, 2023)
This study aims to discover the judge's consideration in the Supreme Court Decision, Number 1400 K/Pdt/1986, and the Supreme Court Decision, Number 1977 K/Pdt/2017 regarding the differences in decisions towards interfaith marriages. Furthermore, the methodology used in this study is the Normative Juridical, namely research in the form of an inventory of applicable laws, which seeks to find the principles or philosophical basis of the law or study in the form of legal efforts findings within a particular case. Based on the result, it may be stated that the regulation of interfaith marriages in Indonesia had legal protection itself in terms of marriage. Nevertheless, the interfaith marriage polemic in terms of its regulation in the marriage's laws is not being strictly regulated and written whether it is prohibited or permitted. Moreover, the inconsistency of marriage law in regulation of interfaith marriage gives rise to a conflict of legal norms in establishing or deciding decision from the state of the court ruling to the supreme court's jurisprudential decision. Abstrak Tujuan dari penelitian ini adalah untuk mengetahui pertimbangan hakim di dalam Putusan Mahkamah Agung Nomor 1400 K/Pdt/1986 dan Putusan Mahkamah Agung Nomor 1977 K/Pdt/2017 terkait perbedaan putusan terhadap perkawinan beda agama. Adapun metodologi yang digunakan dalam penelitian ini adalah metode penelitian Yuridis Normatif, yaitu penelitian berupa inventarisasi perundang-undangan yang berlaku, berupaya mencari asas-asas atau dasar falsafah dari perundang-undangan tersebut, atau penelitian yang berupa usaha penemuan hukum yang sesuai dengan suatu kasus tertentu. Berdasarkan hasil penelitian dapat dikemukakan bahwa Pengaturan Perkawinan beda agama di Indonesia telah mempunyai payung hukum dalam hal perkawinan, namun polemik perkawinan beda agama dalam pengaturannya di Undang-Undang Perkawinan belum diatur secara tegas dan tertulis apakah dilarang atau diperbolehkan pelaksanaannya. Ketidaktegasan Undang-Undang Perkawinan dalam mengatur perkawinan beda agama menimbulkan konflik norma hukum dalam menetapkan atau memutuskan Putusan dari Penetapan Pengadilan Negeri hingga Putusan Yurisprudensi Mahkamah Agung.